1994
DOI: 10.1021/np50106a016
|View full text |Cite
|
Sign up to set email alerts
|

Eudistomin U and Isoeudistomin U, New Alkaloids from the Carribean Ascidian Lissoclinum fragile

Abstract: Chemical investigations of the Caribbean ascidian Lissoclinum fragile (Didemnidae) have resulted in the isolation of new alkaloids which we have designated eudistomin U [1] and isoeudistomin U [2]. Their structures were determined by spectrometric and chemical means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 14 publications
3
47
0
Order By: Relevance
“…In addition, numerous simple or intricate -carboline alkaloids have been isolated and characterized from various marine invertebrates, which include hydroids [212] (Aglaophenia), bryozoans [174,213,214] (Cribricellina, Catenicella), soft corals [215] (Lignopsis), tunicates [216][217][218][219][220][221][222][223][224][225][226] (Eudistoma, Didemnum, Lissoclinum, Ritterella, Pseudodistoma), and various sponges. Marine ascidians belonging to the genus Eudistoma (family Polycitoridae) are another rich source of biologically active -carboline derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous simple or intricate -carboline alkaloids have been isolated and characterized from various marine invertebrates, which include hydroids [212] (Aglaophenia), bryozoans [174,213,214] (Cribricellina, Catenicella), soft corals [215] (Lignopsis), tunicates [216][217][218][219][220][221][222][223][224][225][226] (Eudistoma, Didemnum, Lissoclinum, Ritterella, Pseudodistoma), and various sponges. Marine ascidians belonging to the genus Eudistoma (family Polycitoridae) are another rich source of biologically active -carboline derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…For example, comparison of the biological data of compounds 6 and 19, as well as compounds 16 and 29, revealed that B compounds (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) are not always superior to A compounds (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Both compounds 29 and 19, which contain a 3,4-dihydro-b-carboline skeleton showed notable difference in activity.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Particularly interesting targets include such compounds as eudistomins 7,8) and manzamines, 9,10) which were isolated from marine tunicates and sponges, respectively. As a class, the oxathiazepine containing eudistomines exhibited potent inhibitory activity toward DNA virus HSV-1.…”
mentioning
confidence: 99%
“…Finally, we applied our CH/CH coupling to the synthesis of marine indole alkaloid eudistomin U, 18 which possesses DNA-binding activity (Scheme 3). This short synthesis begins with a MOM protection of commercially available ¢-carboline followed by MTO (methyltrioxorhenium)-catalyzed pyridine oxidation 19 to afford the corresponding N-oxide 4 in 70% yield over two steps.…”
Section: I7kmentioning
confidence: 99%